PENGARUH MEDIA PENDINGIN KADAR AIR GARAM TERHADAP KEKERASAN PADA HASIL PENGELASAN SMAW BAJA KARBON RENDAH - Purbadilaga, Ryan; Firdaus, Firdaus; Suryana, Didi (Politeknik Negeri Sriwijaya, Indonesia, 2022)
Welding in the world of production and maintenance is widely used usually for machine construction in various fields. One of the most widely used materials for machine construction is low carbon steel with a carbon content of 0.05% - 0.30%. In this study, we will provide heat treatment to low carbon steel through a welding process using a cooling medium with variations in salt content. The purpose of this study was to see the effect of heat treatment by welding process on low carbon steel with cooling media with variations in salt water content. The welding method used in this study is the SMAW welding method, with cooling media in the form of: sea water, salt water with variations in salt content (10%, 20%, 30%) with 3 samples for one cooling medium. The hardness test method used is the Rockwell hardness test with tests carried out by taking 5 points for one sample. After testing, it was concluded that the average hardness increased with increasing salt content in the salt solution with the results of the hardness test, namely, seawater cooling media with an average hardness value of 88.37 HRB, cooling media with a salt content of 10% an average value of 88.37 HRB. The hardness produced is 96.6 HRB, the cooling medium with 20% salt content has an average hardness value of 105.83 HRB, the cooling medium with 30% salt content has an average hardness value of 114.1 HRB.